Where wolves don't die eaudiobook - Treuer, Anton (Recorded Books, 2024)
Ezra Cloud hates living in Northeast Minneapolis. His father is a professor of their language, Ojibwe, at a local college, so they have to be there. But Ezra hates the dirty, polluted snow around them. He hates being away from the rez at Nigigoonsiminikaaning First Nation. And he hates the local bully in his neighborhood, Matt Schroeder, who terrorizes Ezra and his friend Nora George. Ezra gets into a terrible fight with Matt at school defending Nora, and that same night, Matt's house burns down. Instantly, Ezra becomes a prime suspect. Knowing he won't get a fair deal, and knowing his innocence, Ezra's family sends him away to run traplines with his grandfather in a remote part of Canada, while the investigation is ongoing. But Matt is looking for him ... From acclaimed author Anton Treuer comes a novel that's both taut thriller and a raw, tender coming-of-age story, about one Ojibwe boy learning to love himself through the love of his family around him.